2023
DOI: 10.2147/jir.s435366
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Body Composition and Systemic Inflammatory Markers in Patients with Locally Advanced Cervical Cancer Following Chemoradiotherapy

Hui Guo,
Shuai Feng,
Zhiqiang Li
et al.

Abstract: Background: Abnormal changes in body composition and systemic inflammation response have been associated with poor survival of cancer patients. Our study was to explore the prognostic value of the association between body composition indicators and systemic inflammation markers among patients with locally advanced cervical cancer (LACC) who underwent concurrent chemoradiotherapy (CCRT). Methods: We retrospectively reviewed medical records of LACC patients treated between 2016 and 2019. Subcutaneous, visceral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…20 Cumulative evidence has indicated a significant association between the SII and survival in cervical cancer. 16,21,22 In this study, it was found that a higher SII was independently associated with poorer OS and PFS. These findings can be attributed to the prognostic value of each SII component.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…20 Cumulative evidence has indicated a significant association between the SII and survival in cervical cancer. 16,21,22 In this study, it was found that a higher SII was independently associated with poorer OS and PFS. These findings can be attributed to the prognostic value of each SII component.…”
Section: Discussionmentioning
confidence: 54%
“…[30][31][32] Similarly, the prognostic value of adiposity in patients with LACC re-mains controversial. 9,22 We speculated that considering individual muscle or fat parameters alone might not accurately describe the distribution of body composition, which could weaken the prognostic prediction ability. Therefore, we investigated the combined index of muscle and fat areas, vFMR, and confirmed its prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [30] conducted an analysis including 196 LACC patients treated with concurrent CRT (Paclitaxel and Cisplatin), and the authors took into account the prognostic value of body composition and systemic inflammatory markers, which is also an SII. Among the other factors, this marker was significantly associated with OS (p = 0.004) in a multivariable model, with a cut-off value of ≥1377.37.…”
Section: Discussionmentioning
confidence: 99%